-16+16t=17t

Simple and best practice solution for -16+16t=17t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16+16t=17t equation:


Simplifying
-16 + 16t = 17t

Solving
-16 + 16t = 17t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-17t' to each side of the equation.
-16 + 16t + -17t = 17t + -17t

Combine like terms: 16t + -17t = -1t
-16 + -1t = 17t + -17t

Combine like terms: 17t + -17t = 0
-16 + -1t = 0

Add '16' to each side of the equation.
-16 + 16 + -1t = 0 + 16

Combine like terms: -16 + 16 = 0
0 + -1t = 0 + 16
-1t = 0 + 16

Combine like terms: 0 + 16 = 16
-1t = 16

Divide each side by '-1'.
t = -16

Simplifying
t = -16

See similar equations:

| 10(r+10)=6(-7-2)-4r | | tan58=6/x | | 9+2(2x+1)=1 | | 5+2k=3 | | 12/3=n | | x^6-2x=0 | | 9u^-4/9u^8 | | 27(p/3)*5(3p).6(2p).4(p) | | 10(r-2)=-5r | | 2u-16=4u-2 | | ln(5x+1)=4 | | z^2+9z=-25 | | 15E+6E=84 | | n/36=1/4 | | 2y=3(4-y) | | -x^2+12x=-19 | | 0.375z+2.25=0.8z-2.4 | | (4x-5)(x-7)=0 | | Sqrt(-x)=-1 | | 5/12=n/6- | | 3/27=9/n | | Ex+x=E | | (3x-5)=ln*306 | | 3x-5=5x+35 | | n/5=24/10 | | 2x+50=2+6x | | G(x)=1.1-ln(2x+5) | | -2x=-x^2-5x+12 | | -7+-18y+18=30y+20+3 | | 5x+y=163 | | 9/n=1/9 | | 6w+0.19=55.39 |

Equations solver categories